Pengembangan Buku Ajar English for Digital Marketing Berbasis Collaborative Learning - Fatimah Nur Arifah; Sri Waluyo (Departement of Mathematics Education, 2023)
This study attempts to develop an English for Digital Marketing textbook based on collaborative learning to support ESP teaching and learning process for non-English study programs especially those concerned in digital marketing. ADDIE model of research and development approach were employed. The stages included data collection and need analysis, textbook design, textbook development, implementation, and evaluation of the textbook use. Participants involved ESP lecturers, 30 students majoring in Informatics, and experts. The test results by the experts indicated validity level of 4.69 which means Very Good with feasibility level of the textbook to be used is 88.66% or Very Feasible. Whereas, the questionnaires distributed to students showed criteria of Very Good with validity level 4.68 and feasibility level of the textbook is 84% or Very Feasible. These results indicate that the textbook developed in this study can be utilized to support the teaching and learning process especially for ESP teaching.